The Leadership, Competency and Certification on Teacher Performance: How the Impact on Vocational Schools Students Achievement in Banten Province Area - E. Nurzaman AM (JTP - Jurnal Teknologi Pendidikan, 2019)
This study aims to determine the effect of principal leadership, competence, and certification on teacher performance, which impact student achievement at Vocational High Schools (SMK) in Banten. The method used is explanatory research with a sample of 88 respondents—the statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results show that the principal's leadership has a significant effect on teacher performance by 35.0%. The hypothesis test obtained a significance of 0.000 <0.05, and competence significantly affects teacher performance by 23.1%. The hypothesis testing obtained a significance of 0.000 <0.05. The results also show, the certification has a significant effect on teacher performance by 23.3%; hypothesis testing is obtaining a significance of 0.000 <0.05. Principal leadership, competence, and certification simultaneously significantly affected teacher performance by 55.9%, hypothesis testing obtained a significance of 0.000 <0.05. Teacher performance significantly affected student achievement by 73.6%; hypothesis testing obtained a significance of 0.000 <0.05